Dosing Optimization for Wafer Weight and Pyramid Formation Improvement - Abdullah, Nur Khairunisa; Mazlan, Muhammad Hazli (Evolution in Electrical and Electronic Engineering, 2023)
This study aimed to optimize the dosage volume of BE baths in solar photovoltaic manufacturing, focusing on the relationship between wafer weight loss and pyramid formation. The primary goals of the research were to examine these relationships and identify the optimal dosing volume for better cell performance. The scope of the research included experimental trials, baseline data comparisons, and analysis using a variety of measurements and software tools such as Precision Balance, Reflectometer, ZETA-20A (3D Microscope), cetisPV-Contact, SPC and JMP software to determine whether the optimal dosing volume could be implemented in production. The research takes into account all of these elements and adheres to accepted methods to guarantee the system's operation. The key results show that when efficiency and short circuit current climb to 0.19% and 0.25%, the system performs better overall and more effectively uses input power. The discussion highlights the achievement in maximizing the BE bath dosing volume and offers recommendations for improving manufacturing while reducing costs and abiding by industry standards.